Measuring recovery: An adapted Brief Assessment of Mood (BAM+) compared to biochemical and power output alterations. Issue 5 (May 2017) - Shearer, David A.; Sparkes, William; Northeast, Jonny; Cunningham, Daniel J.; Cook, Christian J.; Kilduff, Liam P.
Abstract: Objectives: Biochemical (e.g. creatine kinase (CK)) and neuromuscular (e.g. peak power output (PPO)) markers of recovery are expensive and require specialist equipment. Perceptual measures are an effective alternative, yet most validated scales are too long for daily use. Design: This study utilises a longitudinal multi-level design to test an adapted Brief Assessment of Mood (BAM+), with four extra items and a 100 mm visual analogue scale to measure recovery. Methods: Elite under-21 academy soccer players ( N  = 11) were monitored across five games with data (BAM+, CK and PPO) collected for each game at 24 h pre, 24 h and 48 h post-match. Match activity data for each participant was also collected using GPS monitors on players. Results: BAM+, CK and PPO had significant ( p  < .05) linear and quadratic growth curves across time and games that matched the known time reports of fatigue and recovery. Multi-level linear modelling (MLM) with random intercepts for 'participant' and 'game' indicated only CK significantly contributed to the variance of BAM+ scores ( p  < .05). Significant correlations ( p  < .01) were found between changes in BAM+ scores from baseline at 24 and 48 h post-match for total distance covered per minute, high intensity distance covered per minute, and total number of sprints per minute. Conclusions: Visual and inferential results indicate that the BAM+ appears effective for monitoring longitudinal recovery cycles in elite level athletes. Future research is needed to confirm both the scales reliability and validity.